Адаптація України до наслідків зміни клімату - Штець, В.С. (Економіка природокористування і охорони довкілля, 2013)
Розглянуто та проаналізовано стан підготовки національного плану адаптації до зміни клімату в Україні, його проблемні аспекти та перспективи виконання. Оцінено стан навколишнього середовища та можливі загрози в разі бездіяльності, обґрунтовано важливість вжиття адаптаційних заходів. The Author considers and analyzes the status of national adaptation plan preparation in Ukraine, its problems and prospects of implementation. She estimates the status of the environment and possible threats in case of inaction and explains the importance of adaptation measures implementation.
Mitigation and adaptation actions in case of climate change, which Ukraine has to provide are necessary for Ukrainian economy to enhance its efficiency, competitiveness, and to reduce energy dependence, ie they are economically and politically advantageous.
The sooner Ukraine will adapt to climate change, the better we can prevent the threats mentioned in the article. The creation of National adaptation plan, first of all, is one of the steps towards Ukraine's integration into the international community of countries that aspire to sustainable development, which provides a national strategy of harmonizing the interests of economy, society and environment.